Exploring LDLR-APOB Interactions in Familial Hypercholesterolemia in the Vietnamese Population: A Protein-Protein Docking Approach - Ngoc-Thanh Kim; Doan-Loi Do; Mai-Ngoc Thi Nguyen; Hong-An Le; Thanh-Tung Le; Thanh-Huong Truong (Bioinformatics and Biology Insights)
Atherosclerotic cardiovascular diseases (CVDs) are closely linked to factors such as familial hypercholesterolemia (FH), often caused by mutations in low-density lipoprotein receptor ( LDLR ) and apolipoprotein B ( APOB ). Through a comprehensive bioinformatic analysis, we identified novel LDLR and APOB mutations and their cardiovascular disease (CVD) implications, focusing on unique variants in the Vietnamese population. We used homology modeling to predict protein structures; in addition, through protein-protein molecular docking, we assessed how these mutations affect binding affinities. We identified 10 novel binding residues exclusive to the wild-type and precursor LDLR isoforms, including ASP-47, GLY-48, and GLU-51. Analyses of 154 complexes revealed 5 isoforms with low binding affinities and notable hydrogen-bonding interactions—APOB (Arg3527Trp)-LDLR (Cys318Arg), APOB (His3583Leu)-LDLR (Cys104Tyr), APOB wild-LDLR (Glu228Lys), APOB (Phe2469Cys)-LDLR (Glu288Lys), and APOB wild-LDLR (Ser130Ter). These results suggest strong and potentially detrimental interactions among these proteins. Furthermore, they highlight the molecular mechanisms underlying CVD development, reveal potential therapeutic targets, enhance our understanding of genetic variations, and could guide FH research.